Havens are a pathway, not an endpoint, for species recovery: A response to Woinarski et al. (2023) - John L. Read; Kev Bradley; Iain J. Gordon; Adrian D. Manning; Linda E. Neaves; April E. Reside; Kiarrah J. Smith; Rick Southgate; Adrian F. Wayne; Andrew R. Weeks; Belinda A. Wilson; Katherine E. Moseby (Biological Conservation, 2023)

Effectiveness of conservation interventions for Australian woodland birds: A systematic review - Jessica C. Walsh; Michelle R. Gibson; Jeremy S. Simmonds; Helen J. Mayfield; Clare Bracey; Courtney B. Melton; April E. Reside; Martine Maron (Biological Conservation, 2023)

Retaining natural vegetation to safeguard biodiversity and humanity - Jeremy S. Simmonds; Andres Felipe Suarez‐Castro; April E. Reside; James E. M. Watson; James R. Allan; Scott C. Atkinson; Pasquale Borrelli; Nigel Dudley; Stephen Edwards; Richard A. Fuller; Edward T. Game; Simon Linke; et al. (Conservation Biology, 2023)
Global efforts to deliver internationally agreed goals to reduce carbon emissions, halt biodiversity loss, and retain essential ecosystem services have been poorly integrated. These goals rely in part on preserving natural (e.g., native, largely unmodified) and seminatural (e.g., low intensity or sustainable human use) forests, woodlands, and grasslands. To show how to unify these goals, we empirically derived spatially explicit, quantitative, area‐based targets for the retention of natural and seminatural (e.g., native) terrestrial vegetation worldwide. We used a 250‐m‐resolution map of natural and seminatural vegetation cover and, from this, selected areas identified under different international agreements as being important for achieving global biodiversity, carbon, soil, and water targets. At least 67 million km 2 of Earth's terrestrial vegetation (∼79% of the area of vegetation remaining) required retention to contribute to biodiversity, climate, soil, and freshwater conservation objectives under 4 United Nations’ resolutions. This equates to retaining natural and seminatural vegetation across at least 50% of the total terrestrial (excluding Antarctica) surface of Earth. Retention efforts could contribute to multiple goals simultaneously, especially where natural and seminatural vegetation can be managed to achieve cobenefits for biodiversity, carbon storage, and ecosystem service provision. Such management can and should co‐occur and be driven by people who live in and rely on places where natural and sustainably managed vegetation remains in situ and must be complemented by restoration and appropriate management of more human‐modified environments if global goals are to be realized.

Spatial conservation prioritization for locating protected area gaps in Iran - Azadeh Karimi; Hossein Yazdandad; April E. Reside (Biological Conservation, 2023)

Threat-abatement framework confirms habitat retention and invasive species management are critical to conserve Australia's threatened species - Stephen G. Kearney; James E.M. Watson; April E. Reside; Diana O. Fisher; Martine Maron; Tim S. Doherty; Sarah M. Legge; John C.Z. Woinarski; Stephen T. Garnett; Brendan A. Wintle; Euan G. Ritchie; Don A. Driscoll; et al. (Biological Conservation, 2023)

How to prioritize species recovery after a megafire - Michelle Ward; Josie Carwardine; James E. M. Watson; Anna Pintor; Stephanie Stuart; Hugh P. Possingham; Jonathan R. Rhodes; Alexander R. Carey; Nancy Auerbach; April Reside; Chuan Ji Yong; Ayesha I. T. Tulloch (Conservation Biology, 2022)
Due to climate change, megafires are increasingly common and have sudden, extensive impacts on many species over vast areas, leaving decision makers uncertain about how best to prioritize recovery. We devised a decision‐support framework to prioritize conservation actions to improve species outcomes immediately after a megafire. Complementary locations are selected to extend recovery actions across all fire‐affected species’ habitats. We applied our method to areas burned in the 2019−2020 Australian megafires and assessed its conservation advantages by comparing our results with outcomes of a site‐richness approach (i.e., identifying areas that cost‐effectively recover the most species in any one location). We found that 290 threatened species were likely severely affected and will require immediate conservation action to prevent population declines and possible extirpation. We identified 179 subregions, mostly in southeastern Australia, that are key locations to extend actions that benefit multiple species. Cost savings were over AU$300 million to reduce 95% of threats across all species. Our complementarity‐based prioritization also spread postfire management actions across a wider proportion of the study area compared with the site‐richness method (43% vs. 37% of the landscape managed, respectively) and put more of each species’ range under management (average 90% vs. 79% of every species’ habitat managed). In addition to wildfire response, our framework can be used to prioritize conservation actions that will best mitigate threats affecting species following other extreme environmental events (e.g., floods and drought).

Communicating the true challenges of saving species: response to Wiedenfeld et al. - James E. M. Watson; Jeremy S. Simmonds; Michelle Ward; Chuan J. Yong; April E. Reside; Hugh P. Possingham; Andrew Rogers; Josie Carwardine (Conservation Biology, 2022)

Accelerated shifts in terrestrial life zones under rapid climate change - Paul R. Elsen; Earl C. Saxon; B. Alexander Simmons; Michelle Ward; Brooke A. Williams; Hedley S. Grantham; Salit Kark; Noam Levin; Katharina‐Victoria Perez‐Hammerle; April E. Reside; James E. M. Watson (Global Change Biology, 2022)
Rapid climate change is impacting biodiversity, ecosystem function, and human well‐being. Though the magnitude and trajectory of climate change are becoming clearer, our understanding of how these changes reshape terrestrial life zones—distinct biogeographic units characterized by biotemperature, precipitation, and aridity representing broad‐scale ecosystem types—is limited. To address this gap, we used high‐resolution historical climatologies and climate projections to determine the global distribution of historical (1901–1920), contemporary (1979–2013), and future (2061–2080) life zones. Comparing the historical and contemporary distributions shows that changes from one life zone to another during the 20th century impacted 27 million km 2 (18.3% of land), with consequences for social and ecological systems. Such changes took place in all biomes, most notably in Boreal Forests, Temperate Coniferous Forests, and Tropical Coniferous Forests. Comparing the contemporary and future life zone distributions shows the pace of life zone changes accelerating rapidly in the 21st century. By 2070, such changes would impact an additional 62 million km 2 (42.6% of land) under “business‐as‐usual” (RCP8.5) emissions scenarios. Accelerated rates of change are observed in hundreds of ecoregions across all biomes except Tropical Coniferous Forests. While only 30 ecoregions (3.5%) had over half of their areas change to a different life zone during the 20th century, by 2070 this number is projected to climb to 111 ecoregions (13.1%) under RCP4.5 and 281 ecoregions (33.2%) under RCP8.5. We identified weak correlations between life zone change and threatened vertebrate richness, levels of vertebrate endemism, cropland extent, and human population densities within ecoregions, illustrating the ubiquitous risks of life zone changes to diverse social–ecological systems. The accelerated pace of life zone changes will increasingly challenge adaptive conservation and sustainable development strategies that incorrectly assume current ecological patterns and livelihood provisioning systems will persist.

Persistence through tough times: fixed and shifting refuges in threatened species conservation - April E. Reside; Natalie J. Briscoe; Chris R. Dickman; Aaron C. Greenville; Bronwyn A. Hradsky; Salit Kark; Michael R. Kearney; Alex S. Kutt; Dale G. Nimmo; Chris R. Pavey; John L. Read; Euan G. Ritchie; et al. (Biodiversity and Conservation, 2019)

Adapting systematic conservation planning for climate change - April E. Reside; Nathalie Butt; Vanessa M. Adams (Biodiversity and Conservation, 2018)

Sink or swim? Potential for high faunal turnover in Australian rivers under climate change - Cassandra S. James; April E. Reside; Jeremy VanDerWal; Richard G. Pearson; Damien Burrows; Samantha J. Capon; Thomas D. Harwood; Lauren Hodgson; Nathan J. Waltham (Journal of Biogeography, 2017)
Aim Climate change threatens biodiversity in all ecosystems, and major shifts in species distributions are expected. Freshwater ecosystems are considered particularly vulnerable due to the ectothermic physiology of most freshwater species and their limited habitat extent and capacity to track climate trends. In this study, we examined what broad patterns in freshwater riverine species turnover might be expected under climate change across continental Australia and what are the implications of these patterns for aquatic species and the low aquatic biodiversity of some bioregions? Location Continental Australia. Methods We built statistical relationships between bioclimatic environments and the occurrence of species of four freshwater taxa (freshwater fish, crayfish, turtles and frogs) and examined trends in projected species turnover for a ‘business as usual’ climate scenario. We used Maxent to model species distributions and present the median projection across 18 global climate models. A recently derived national stream network was used to generate estimates of mean annual river flow and to produce realistic species distributions and migration options by restricting dispersal and migration opportunities usually available to riverine fauna. Results High species turnover was driven overwhelmingly by potential local extinctions particularly for stream frogs and crayfish where their current biodiversity is largely confined to higher elevation headwater streams. We predicted high turnover for inland regions of Australia, which are arid and generally support fewer freshwater species. Main conclusions Our analysis indicates that under the most severe emissions pathway, projected climate change is likely to cause substantial changes to the composition of faunal assemblages in Australian rivers well before the end of this century. While freshwater systems globally are subject to immediate and pressing threats from anthropogenic land and water use, management interventions addressing these pressures need to be considered within the context of climate change.

Dynamic habitat suitability modelling reveals rapid poleward distribution shift in a mobile apex predator - Nicholas J. Hill; Andrew J. Tobin; April E. Reside; Julian G. Pepperell; Tom C. L. Bridge (Global Change Biology, 2016)
Many taxa are undergoing distribution shifts in response to anthropogenic climate change. However, detecting a climate signal in mobile species is difficult due to their wide‐ranging, patchy distributions, often driven by natural climate variability. For example, difficulties associated with assessing pelagic fish distributions have rendered fisheries management ill‐equipped to adapt to the challenges posed by climate change, leaving pelagic species and ecosystems vulnerable. Here, we demonstrate the value of citizen science data for modelling the dynamic habitat suitability of a mobile pelagic predator (black marlin, Istiompax indica ) within the south‐west Pacific Ocean. The extensive spatial and temporal coverage of our occurrence data set ( n = 18 717), collected at high resolution (~1.85 km 2 ), enabled identification of suitable habitat at monthly time steps over a 16‐year period (1998–2013). We identified considerable monthly, seasonal and interannual variability in the extent and distribution of suitable habitat, predominately driven by chlorophyll a and sea surface height. Interannual variability correlated with El Nino Southern Oscillation ( ENSO ) events, with suitable habitat extending up to ~300 km further south during La Nina events. Despite the strong influence of ENSO , our model revealed a rapid poleward shift in the geometric mean of black marlin habitat, occurring at 88.2 km decade −1 . By incorporating multiple environmental factors at monthly time steps, we were able to demonstrate a rapid distribution shift in a mobile pelagic species. Our findings suggest that the rapid velocity of climate change in the south‐west Pacific Ocean is likely affecting mobile pelagic species, indicating that they may be more vulnerable to climate change than previously thought.

Immigrants and refugees: the importance of dispersal in mediating biotic attrition under climate change - Alex S. Anderson; April E. Reside; Jeremy J. VanDerWal; Luke P. Shoo; Richard G. Pearson; Stephen E. Williams (Global Change Biology, 2012)
Montane tropical rainforests are critically important areas for global bird diversity, but are projected to be highly vulnerable to contemporary climate change. Upslope shifts of lowland species may partially offset declines in upland species but also result in a process of lowland biotic attrition. This latter process is contingent on the absence of species adapted to novel warm climates, and isolation from pools of potential colonizers. In the A ustralian Wet Tropics, species distribution modelling has forecast critical declines in suitable environmental area for upland endemic birds, raising the question of the future role of both natural and assisted dispersal in species survival, but information is lacking for important neighbouring rainforest regions. Here we use expanded geographic coverage of data to model the realized distributions of 120 bird species found in north‐eastern A ustralian rainforest, including species from potential source locations in the north and recipient locations in the south. We reaffirm previous conclusions as to the high vulnerability of this fauna to global warming, and extend the list of species whose suitable environmental area is projected to decrease. However, we find that expansion of suitable area for some species currently restricted to northern rainforests has the potential to offset biotic attrition in lowland forest of the A ustralian Wet Tropics. By examining contrasting dispersal scenarios, we show that responses to climate change in this region may critically depend on dispersal limitation, as climate change shifts the suitable environmental envelopes of many species south into currently unsuitable habitats. For lowland and northern species, future change in vegetation connectivity across contemporary habitat barriers is likely to be an important mediator of climate change impacts. In contrast, upland species are projected to become increasingly isolated and restricted. Their survival is likely to be more dependent on the viability of assisted migration, and the emergence and persistence of suitable environments at recipient locations.

Multiscale topoedaphic heterogeneity increases resilience and resistance of a dominant grassland species to extreme drought and climate change - ROBERT GODFREE; BRENDAN LEPSCHI; APRIL RESIDE; TERRY BOLGER; BRUCE ROBERTSON; DAVID MARSHALL; MALCOLM CARNEGIE (Global Change Biology, 2011)
It is argued that the inclusion of spatially heterogeneous environments in biodiversity reserves will be an effective means of encouraging ecosystem resilience and plant community conservation under climate change. However, the resilience and resistance of plant populations to global change, the specific life‐history traits involved and the spatial scale at which environmentally driven demographic variation is expressed remains largely unknown for most plant groups. Here we address these questions by reporting an empirical investigation into the impacts of an unprecedented 3‐year drought on the demography, population growth rates ( λ ) and biogeographical distribution of core populations of the perennial grassland species Austrostipa aristiglumis in semiarid Australia. We use life‐history analysis and periodic matrix population models to specifically test the hypothesis that patch‐ and habitat‐scale variation in vital life‐history parameters result in spatial differences in the resilience and resistance of A. aristiglumis populations to extreme drought. We show that the development of critical soil water deficits during drought resulted in collapse of adult A. aristiglumis populations ( λ ≪1), rapid interhabitat phytosociological change and overall contraction towards mesic refugia where populations were both more resistant and resilient to perturbation. Population models, combined with climatic niche analysis, suggest that, even in core areas, a significant reduction in size and habitat range of A. aristiglumis populations is likely under climate change expected this century. Remarkably, however, we show that even minor topographic variation (0.2–3 m) can generate significant variation in demographic parameters that confer population‐level resilience and resistance to drought. Our findings support the hypothesis that extreme climatic events have the capacity to induce rapid, landscape‐level shifts in core plant populations, but that the protection of topographically heterogeneous environments, even at small spatial scales, may play a key role in conserving biodiversity under climate change in the coming century.